Far but close: how leaders can strengthen social identification with virtual teams - Wilbert, Jana B.; Wesche, Jenny Sarah; Handke, Lisa; Kerschreiter, Rudolf (Behaviour & Information Technology, 2023)
As modern work is increasingly characterised by virtual collaboration, leaders have to coordinate teams across multiple work sites. One way to align dispersed team members towards collective goals is to strengthen their identification with the team. However, little is known about how to strengthen identification in virtual teams that do not share a physical environment. We conducted interviews based on the critical incident technique with 26 virtual leaders and 20 virtual team members. Qualitative content analysis revealed six categories of leader behaviour: 1) define the team, 2) strengthen team interdependence, 3) emphasise the team as a whole, 4) empower the team, 5) recognise team effort, and 6) stimulate informal team exchange. By mapping previous research and our findings onto a tridimensional model of social identification, we highlight both, behaviour similar to face-to-face leader behaviour and behaviour unique to the virtual context, and provide concrete behaviours for leadership practice and intervention studies.
CRIS-Team Scopus Importer:2023-11-03
Keywords: leader behaviour; online collaboration; Social identification; social identity; virtual leadership; virtual teams